Testing method for acidity value and bonding performance of phenolic foam materials

By using neutral borax buffer solution in phenolic foam materials to impregnate and dissolve acidic substances, the problem of cumbersome and time-consuming acidity testing of phenolic foam materials in the prior art is solved, and the acidity value is fast and accurate detection is achieved, and the correlation with the bonding performance is high, which has important application value.

CN115902178BActive Publication Date: 2025-04-11BEIJING BUILDING MATERIAL INSPECTION RES INST CO LT
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211262190.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-14
Publication Date
2025-04-11
Estimated Expiration
2042-10-14

AI Technical Summary

Technical Problem

In the prior art, the acidity testing steps of phenolic foam materials are complicated, time-consuming and low accuracy, making it difficult to quickly and accurately evaluate their acidity value and bonding properties.

Method used

The acidic substances in the phenolic foam material were impregnated with neutral borax buffer solution, and the acidic substances were dissolved by stirring and mixing. The pH value of the solution was then tested to determine the acidity value. This method does not require the use of organic solvents and is suitable for testing of foam materials.

Benefits of technology

It has achieved rapid and accurate testing of the acidity value of phenolic foam materials, and the test results are highly consistent with the bonding performance. It can scientifically and reasonably guide the evaluation of bonding performance of the material, and has important application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115902178B_ABST
    Figure CN115902178B_ABST
Patent Text Reader

Abstract

The present invention provides a method for detecting the acidity value and bonding performance of a phenolic foam material, comprising: sampling from the phenolic foam material, grinding to a preset particle size, and then placing in a borax buffer solution with a pH value of 7±0.5, stirring and mixing, so that the acidic substance in the phenolic foam material is impregnated and precipitated, and then testing the pH value of the solution, which is the acidity value of the phenolic foam material. The present invention can solve the defects of the prior art that the acidity test steps of phenolic foam thermal insulation materials are complicated, time-consuming, and low in accuracy, and realizes rapid and accurate testing of the acidity value of phenolic foam materials, and is green and environmentally friendly. The test results are highly consistent with the bonding properties of the phenolic foam materials, so that the bonding properties of such materials can be scientifically and reasonably evaluated and guided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material performance testing, and in particular to a method for detecting the acidity value and bonding performance of a phenolic foam material. Background Art

[0002] At present, the insulation materials commonly used for building exterior insulation are mainly divided into two categories: inorganic and organic. Inorganic materials such as rock wool, glass wool, foam glass, foam cement, etc. have a combustion performance of Class A and good fire resistance, but the thermal conductivity is large, the insulation effect is not ideal, and it is difficult to meet the increasingly high energy-saving standards. Organic materials such as EPS, XPS and PU boards are light in weight, have good insulation and heat insulation effects, and are widely used in engineering practice. However, its biggest defect is poor fire safety, easy aging and easy burning. Thermosetting rigid phenolic foam insulation board material has good flame retardancy, and its combustion performance reaches Class B1. The material is not easy to burn when it encounters a flame source. It only burns or smolders at above 400°C, without flame, and almost all chars. The smoke volume is extremely low, and almost no toxic gases such as carbon monoxide are produced. After a 25 mm thick phenolic foam flat plate is subjected to a 1700°C flame spray for 10 minutes, only the surface is slightly carbonized and will not be burned through, which can effectively prevent the occurrence and spread of fire. Therefore, phenolic foam insulation board exterior wall insulation materials are of great significance to improving the energy saving and fire safety of building insulation systems, avoiding fires, and reducing economic losses, major casualties and environmental pollution.

[0003] However, a certain amount of acidic substances need to be added to the thermosetting rigid phenolic foam insulation board during the production process for curing, so that the thermosetting rigid phenolic foam insulation board has a certain acidity, and the pH value is generally 3-5. When the thermosetting rigid phenolic foam insulation board is used in the external insulation project of the building exterior wall, the thin plastering external insulation system formed by the bonding mortar as the bonding layer and the plastering mortar as the protective layer is bonded and fixed to the wall, so that the surface of the thermosetting rigid phenolic foam insulation board and the mortar interface are prone to acid-base reaction, thereby greatly reducing the bonding strength of the phenolic insulation board system, and then affecting the application of the thermosetting rigid phenolic foam insulation board in the external insulation of the building. Therefore, it is particularly important to control the acidity of the thermosetting rigid phenolic foam insulation board to regulate its bonding performance when used for the insulation of the building exterior wall.

[0004] Prior art generally refers to standard GB / T32364 "the mensuration of the pH value of plastic phenolic resin" to test the pH value of thermosetting rigid phenolic foam insulation board, but the method is mainly applicable to phenolic solid resin, needs to adopt organic solvent to dissolve phenolic solid resin, then test its acidity, whole testing process is loaded down with trivial details, complicated, inefficient. Although this kind of detection method can dissolve the acidic substance in phenolic solid resin, in actual applications, in view of the impact of acidic substance on bonding performance (mainly the acidic substance that is easier to precipitate quickly has a greater impact on bonding performance), it is not necessary to dissolve all acidic substances and test again. Moreover, phenolic foam is not easy to dissolve, and the method is actually not suitable for foam materials, and the test result deviation is relatively large, and it takes a long time, which is unfavorable for the evaluation of the bonding performance of phenolic insulation materials in actual applications. Summary of the invention

[0005] The invention provides a method for detecting the acidity value and bonding performance of a phenolic foam material, so as to solve the defects of the prior art that the acidity test of the phenolic foam material is complicated, time-consuming and low in accuracy, and realizes rapid and accurate testing of the acidity value of the phenolic foam material, and is green and environmentally friendly. The test result is highly consistent with the bonding performance of the phenolic foam material, so that scientific and reasonable guidance can be provided on the bonding performance of such materials.

[0006] The present invention provides a method for detecting the acidity value of a phenolic foam material, comprising: sampling from the phenolic foam material, grinding to a particle size of less than 5 mm, and then placing in a borax buffer solution with a pH value of 7±0.5, stirring and mixing, so that the acidic substance in the phenolic foam material is impregnated and precipitated, and then testing the pH value of the solution, which is the acidity value of the phenolic foam material. Based on the characteristic that the porous structure of the phenolic foam material makes it easier for the acidic substance to be leached, the present invention uses a neutral borax buffer solution to impregnate the phenolic foam so that the acidic substance is dissolved, and there is no need to use an organic solvent to completely dissolve the phenolic solid resin, thereby overcoming the technical bias in the test standard; then testing its pH value, and by comparing it with the bonding performance, it is shown that the detection method of the present invention has a high degree of consistency with the bonding strength, can be used for indirect evaluation of the bonding performance of phenolic foam in practical applications, and has a fast test speed and high accuracy, and has important application value.

[0007] As a further improvement of the present invention, the stirring and mixing time increases with the increase of the preset particle size, and the preset particle size is less than 5 mm. By controlling the particle size and the immersion time, the correlation between the pH value finally measured and the bonding strength is maximized, that is, the evaluation is most accurate and takes less time.

[0008] As a further improvement of the present invention, the acidic substance in the phenolic foam material is impregnated and dissolved by stirring and mixing; when the sample particle size is 2-5mm, the stirring and mixing time is 20min±1; when the sample particle size is 1-2mm, the stirring and mixing time is 15min±1; when the sample particle size is 0.5-1mm, the stirring and mixing time is 10min±1; when the sample particle size is less than 0.5mm, the stirring and mixing time is 5min±0.5. The present invention summarizes the relationship between the phenolic foam particle size and the stirring and mixing time through multiple groups of experiments. Within the above-mentioned limited range, the measured pH value has the greatest correlation with the bonding strength, and the time is short. The pH value test can be used to quickly and reasonably evaluate the bonding properties of the phenolic foam, thereby guiding the molding process of the thermal insulation material.

[0009] As a further improvement of the present invention, the mass volume ratio of the total sampled mass of the phenolic foam material to the borax buffer solution is 0.1-0.3 g / mL. By controlling the impregnation concentration of the phenolic foam, the impregnation speed can be easily regulated.

[0010] As a further improvement of the present invention, the solute of the borax buffer solution includes borax and boric acid; the concentration of the borax is 3-5 g / L, and the concentration of the boric acid is 3-5 g / L.

[0011] As a further improvement of the present invention, the preparation method of the borax buffer solution includes: dissolving the dried borax and boric acid in deionized water, adjusting the pH value thereof to 7±0.5, and then diluting to 1000 mL to obtain the borax buffer solution.

[0012] As a further improvement of the present invention, the sampling includes: dividing the phenolic foam material into 3-10 areas, preferably 5-8 areas, and then sampling from each area with a medium mass, and the total sampling mass is 50-200g, preferably 100g. By uniform sampling, the test deviation problem caused by uneven materials is avoided.

[0013] As a further improvement of the present invention, the sampling includes: sampling the phenolic foam material (for example, the aspect ratio is 3:2), drawing a vertical vertical line at the 2 / 9 position of both ends of the long side, drawing a horizontal vertical line at the 1 / 6 position of both ends of the short side, connecting the two diagonal lines, and taking the four intersections of the two vertical vertical lines and the horizontal vertical lines and the intersection of the two diagonal lines as sampling points, and sampling 20g at each sampling point. Figure 1 As shown, this sampling method is fast and can more accurately represent the acidity value of the entire sample.

[0014] As a further improvement of the present invention, the acidic substance includes one or more of sulfuric acid, phosphoric acid, benzenesulfonic acid (such as toluenesulfonic acid, phenolsulfonic acid, etc.). Such acidic substances can be gradually dissolved in the above-mentioned borax buffer solution without destroying the structure of the phenolic foam itself, thereby reducing the influence of other acidic impurities that are not easy to migrate out on the test results.

[0015] As a further improvement of the present invention, the pH value detection method of the solution includes a pH meter or a pH test paper test, wherein the pH test paper test is to use a pH test paper to test and then compare with a standard colorimetric card to determine the pH value of the solution.

[0016] The present invention also provides a method for detecting the bonding performance of a phenolic foam material. The bonding performance of the phenolic foam material is evaluated according to the pH value obtained by the above-mentioned method for detecting the acidity value of the phenolic foam material. The smaller the pH value of the phenolic foam material, the worse its bonding performance with the mortar.

[0017] The beneficial effects of the present invention are as follows:

[0018] The method for detecting the acidity value of the phenolic foam material provided by the present invention is based on the characteristic that the porous structure of the phenolic foam material makes it easier for the acidic substance to leach out. The phenolic foam is impregnated with a neutral borax buffer solution to dissolve the acidic substance, and then the pH value thereof is tested. The detection method has a high degree of consistency with the bonding strength, can be used for indirect evaluation of the bonding performance of the phenolic foam in practical applications, and has a fast test speed and high accuracy, and has important application value. Moreover, the method provided by the present invention does not need to use an organic solvent, and is therefore green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 A schematic diagram of the locations of sampling points for the method for detecting the acidity value of a phenolic foam material provided by the present invention. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Combine the following Figure 1 Describe the detection method of the acidity value of the phenolic foam material of the present invention, Examples 1-28

[0023] A method for detecting the acidity value of a phenolic foam insulation material comprises: dividing a 600 mm×900 mm phenolic foam insulation board into five areas, taking out 20 g of a sample from each area, grinding it in a mortar to a preset particle size, putting it into 500 mL of a borax buffer solution (composed of 3.39 g / L borax and 3.53 g / L boric acid) with a pH value of 7, stirring and mixing, and then testing the pH value of the solution, which is the acidity value of the phenolic foam material. Specific test parameters are shown in Table 1.

[0024] Table 1 Test process parameters and test results of Examples 1-28

[0025]

[0026]

[0027] As can be seen from Table 1, the phenolic foam granularity is smaller, and the stirring and mixing time required for measuring its true leaching acidity value is shorter, but the overall time is all below 30min, which shows that the testing method of the present invention is fast. For the foam of the same particle size, the pH value slightly reduces with the prolongation of the mixing time, which shows that the acidic components can be progressively dissolved in the borax buffer selected by the present invention, and the acidity value measured by this method can directly match with the bonding strength. In actual use, suitable particle size and time can be selected according to the method design provided by the present invention, thereby the acidity value of the fast-test phenolic foam material can be evaluated.

[0028] Examples 29-32

[0029] A method for detecting the acidity of a phenolic foam material, according to the test parameters of Example 3, tests the acidity of different batches of phenolic foam insulation boards. The method comprises: dividing a 600 mm×900 mm phenolic foam insulation board into five areas, taking out 20 g of a sample from each area, grinding it in a mortar to an average particle size of 0.2 mm, putting it into 500 mL of a borax buffer solution (composed of 3.39 g / L borax and 3.53 g / L boric acid) with a pH value of 7, stirring and mixing for 5 minutes, and then testing the pH value of the solution, which is the acidity of the phenolic foam material.

[0030] Table 2 Test results of Examples 29-32

[0031]

[0032] It can be seen from Table 2 that the pH of the phenolic foam insulation board has a great influence on the tensile bond strength of the mortar. The smaller the pH value, the lower the tensile bond strength between the mortar. It can be seen that the acidity value measured by the present invention is highly consistent with the change trend of the bond strength. Therefore, in actual use, the bond strength can be indirectly evaluated by the acidity value measured by the present invention, without the need for testing by the standard dissolution method, so that the appropriate phenolic foam insulation material can be quickly selected, and the actual bonding process can be adaptively adjusted, so it is highly practical.

[0033] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for detecting the acidity value of a phenolic foam material, characterized in that: include: Sampling is taken from the phenolic foam material, the sample particle size is controlled to be less than 5 mm, and the sample is immersed in a borax buffer solution with a pH value of 7±0.5 to dissolve the acidic substance, and then the pH value of the solution is tested, which is the acidity value of the phenolic foam material; the solute of the borax buffer solution includes borax and boric acid, the concentration of the borax is 3-5 g / L, and the concentration of the boric acid is 3-5 g / L.

2. The method for detecting the acidity value of the phenolic foam material according to claim 1, characterized in that: The mass volume ratio of the total sampled mass of the phenolic foam material to the borax buffer solution is 0.1-0.3 g / mL.

3. The method for detecting the acidity value of the phenolic foam material according to claim 1, characterized in that: The immersion and dissolution time increases with the increase of the particle size of the sample.

4. The method for detecting the acidity value of the phenolic foam material according to claim 3, characterized in that: By stirring and mixing, the acidic substance in the phenolic foam material is impregnated and dissolved; When the sample particle size is 2-5mm, the stirring and mixing time is 20min±1; when the sample particle size is 1-2mm, the stirring and mixing time is 15min±1; when the sample particle size is 0.5-1mm, the stirring and mixing time is 10min±1; when the sample particle size is less than 0.5mm, the stirring and mixing time is 5min±0.

5.

5. The method for detecting the acidity value of a phenolic foam material according to any one of claims 1 to 4, characterized in that: The sampling comprises: dividing the phenolic foam material into 3-10 regions, and then sampling with a medium mass from each of the regions, with the total sampling mass being 50-200 g.

6. The method for detecting the acidity value of the phenolic foam material according to claim 5, characterized in that: The sampling includes: sampling the phenolic foam material, drawing a longitudinal vertical line at the 2 / 9 position at both ends of its long side, drawing a transverse vertical line at the 1 / 6 position at both ends of its short side, connecting the two diagonal lines, and taking the four intersections of the two longitudinal vertical lines and the transverse vertical line and the intersection of the two diagonal lines as sampling points, and sampling 20g at each sampling point.

7. The method for detecting the acidity value of phenolic foam material according to claim 1, characterized in that: The acidic substance includes one or more of sulfuric acid, phosphoric acid, and benzenesulfonic acid; the pH value detection method of the solution includes pH meter or pH test paper testing.

8. A method for detecting the bonding performance of a phenolic foam material, characterized in that: The pH value obtained by the method for detecting the acidity value of the phenolic foam material according to any one of claims 1 to 7 is used to evaluate the adhesion of the phenolic foam material. The smaller the pH value of the phenolic foam material, the worse its adhesion.

Citation Information

Patent Citations

  • Preparation method of low acidic phenolic foam insulation material

    CN105732923A